2016
DOI: 10.1152/ajplung.00422.2015
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte transport properties in distal small airways from cystic fibrosis pigs with implications for host defense

Abstract: While pathological and clinical data suggest that small airways are involved in early cystic fibrosis (CF) lung disease development, little is known about how the lack of cystic fibrosis transmembrane conductance regulator (CFTR) function contributes to disease pathogenesis in these small airways. Large and small airway epithelia are exposed to different airflow velocities, temperatures, humidity, and CO2 concentrations. The cellular composition of these two regions is different, and small airways lack submuco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 69 publications
1
55
0
Order By: Relevance
“…We first assessed mRNA transcripts of carbonic anhydrase isozymes ( Ca ) predicted to be enzymatically active outside of cells, which include the membrane‐bound and secreted carbonic anhydrase isozymes. Microarray analysis from Li et al (Fig. D) revealed that most mRNA transcripts for these isozymes were present at levels lower than Cftr mRNA transcripts, which is present in low abundance in airway epithelia (Trapnell et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We first assessed mRNA transcripts of carbonic anhydrase isozymes ( Ca ) predicted to be enzymatically active outside of cells, which include the membrane‐bound and secreted carbonic anhydrase isozymes. Microarray analysis from Li et al (Fig. D) revealed that most mRNA transcripts for these isozymes were present at levels lower than Cftr mRNA transcripts, which is present in low abundance in airway epithelia (Trapnell et al.…”
Section: Resultsmentioning
confidence: 99%
“…Piglet lungs were excised and proximal large airways, including trachea and main stem bronchi, were dissected out from the airway tree as described (Li et al. ). Next, primary porcine airway epithelia were isolated according to an adapted procedure originally developed for tracheal airway cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormally acidic ASL pH results from loss of CFTR-mediated HCO 3 − secretion in the presence of continued H + secretion (35). CFTR is also key for HCO 3 − secretion and alkalization of ASL pH in small airways (36).…”
mentioning
confidence: 99%
“…An important feature of these models is the presence of submucosal glands (SMGs) throughout the proximal airways. CF airway pathology is largely attributed to defects in the SMGs as CFTR dysfunction is associated with abnormal mucus secretion and defective innate immunity . SMGs are therefore proposed as one of the targets for gene therapy.…”
Section: A New Era Of Cf Animal Models and Read‐outs To Study The Halmentioning
confidence: 99%